PERIKANAN TONGKOL DI PERAIRAN BUYAT PANTE - Sompie, Meta S (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2011)
ABSTRACTFisheries development in Indonesia, especially in North Sulawesi, is to optimize the utilization of resources through a comprehensively integrated approach and accommodate a variety of interests, such as fishermen, national economy, sustainability of marine resources and fisheries, and environmental balance and sustainability. For fisheries policy preparation, adequate information on fish resources is required. One of the fish resources in Buyat Bay area is little tuna (Auxis thazard). This study aimed to evaluate the little tuna resource and fishing season in the waters of Buyat Bay and surrounding areas. The fishing area in Buyat Bay waters is 4.88 km2. The little tuna biomass of Buyat Bay is 0.486 ton/km2. Monthly average catch was 0.7 tons relative to the maximum sustainable catch of 2.37 ton/month, and then the exploitation rate was 29.59%. This meant that the catch landed in Buyat Pante was lower than the monthly maximum sustainable catch. The catch is allowed at 80% of the maximum sustainable catch, which amounted to 1.89 tons/month. Tuna fishing season in Buyat Bay occurred in March and then from May to September following the pattern of the two-month season of the year for high density.ABSTRAKPembangunan perikanan di Indonesia, khususnya di Sulawesi Utara adalah mengoptimalkan pemanfaatan sumberdaya melalui pendekatan yang terintegrasi dengan komprehensif dan mengakomodasi berbagai kepentingan, yaitu: nelayan, ekonomi nasional, kelestarian sumberdaya kelautan dan perikanan, serta keseimbangan dan kelestarian lingkungan. Untuk penyusunan kebijakan perikanan diperlukan informasi yang memadai dari sumberdaya ikan. Salah satu sumberdaya ikan di wilayah Teluk Buyat adalah ikan tongkol (Auxis thazard). Penelitian ini bertujuan untuk mengevaluasi sumberdaya dan musim penangkapan ikan di perairan Teluk Buyat dan sekitarnya. Area penangkapan ikan di perairan Teluk Buyat (4,88 km2). Biomassa ikan ini di Teluk Buyat 0,486 ton/km2. Tangkapan rata-rata bulanan sebesar 0,7 ton, dibandingkan dengan hasil tangkapan maksimum yang lestari dari 2,37 ton/bulan, kemudian tingkat pemanfaatan ikan tuna di Teluk Buyat berada pada 29,59%. Ini berarti bahwa hasil tangkapan yang didaratkan oleh para nelayan Buyat Pante masih berada di bawah eksploitasi. Hasil tangkapan yang diperbolehkan sebesar 80% dari hasil tangkapan maksimum lestari (1,89 ton/bulan). Musim penangkapan tuna di Teluk Buyat terjadi selama enam bulan, yang dimulai dari bulan Maret dan selanjutnya dari bulan Mei hingga September, mengikuti pola musim dua bulan dalam setahun dengan kepadatan tinggi.